Between Imperium and Sacerdotium: On the Dialectics of Religious Freedom, with Special Reference to the South African Context - Delport, Khegan (Religion & theology, 2022)
Christianity from its inception has expressed a tension between imperium and sacerdotium; after the Reformation, this tension has only been aggravated. Avowals of religious freedom thereafter have often rightly insisted on the capacity of spiritual communities to invoke limits for the state. This is readily apparent in South Africa, past and present. However, scholarship has shown that “religious liberty” has an ambiguous function, such as its privatisation of belief, based on a liberalised notion of “negative” freedom that allows the state to grant the “right” to “belief,” while simultaneously rendering belief a purely private or “otherworldly” affair. This is traceable to overly-Protestant conceptions of “religion” and “freedom” that are pervasive – including South Africa. From a theological perspective, I argue that this conception of “religious freedom” might sit in tension with aspects of ecclesiology and that the discursive deployment of “religious freedom” should therefore be engaged critically.